A Neurofibromatosis Noonan Syndrome Patient Presenting with Abnormal External Genitalia - Esra Işık; Hüseyin Onay; Tahir Atik; Aslı Ece Solmaz; Samim Özen; Özgür Çoğulu; Şükran Darcan; Ferda Özkınay (Galenos Yayincilik, 2020)
Neurofibromatosis Noonan syndrome (NFNS) is a rare RASopathy syndrome, resulting from NF1 gene mutations. NFNS is characterized by phenotypic features of both neurofibromatosis type 1 (NF1) and Noonan syndrome. Plexiform neurofibromas (PNFs) are an unusual finding in NFNS. A seven year-old girl with typical clinical features of NF1 was referred to our clinic due to short stature and abnormal genital appearance. Due to dysmorphic features, a clinical diagnosis of NFNS was considered in the patient and, following molecular analysis, revealed a novel heterozygous c.3052_3056delTTAGT (p.L1018X) variant in the NF1 gene. Although evaluation for genital virilization, including karyotype and hormonal studies were normal, imaging studies revealed a diffuse genital PNF. Although PNFs are seen rarely in NFNS, this should be considered in the differential diagnosis of genital virilization in these patients to prevent unnecessary testing.